2014
DOI: 10.1086/677260
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroid Hormones Link the Juvenile Environment to Alternative Adult Life Histories in a Seasonal Insect

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: The conditional expression of alternative life strategies is a widespread feature of animal life and a pivotal adaptation to life in seasonal environments. To optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 54 publications
4
38
0
Order By: Relevance
“…During reproductive diapause, the development of oogenesis, vitellogenesis, accessory glands, and mating behaviour is arrested (Tatar & Yin, 2001;Tauber et al, 1986). In Bicyclus butterflies, B. anynana in particular, when entering reproductive diapause, females arrest reproduction coupled with changes in other traits such as cryptic colour pattern, large body size, increased fat deposits, increased longevity, and reduced behavioural activity for the entire dry season until the onset of the rains (Brakefield & Reitsma, 1991;Oostra et al, 2014;van Bergen et al, 2017). The induction of diapause and correlated expression of relevant traits is dependent on the availability of environmental cues, mainly temperature in the case of B. anynana, that reliably predict the future adult environment (Brakefield & Reitsma, 1991; for temperate insects, see Nylin, 2013).…”
Section: Species Of the African Mycalesina Genus Bicyclus Inhabit Bothmentioning
confidence: 99%
See 1 more Smart Citation
“…During reproductive diapause, the development of oogenesis, vitellogenesis, accessory glands, and mating behaviour is arrested (Tatar & Yin, 2001;Tauber et al, 1986). In Bicyclus butterflies, B. anynana in particular, when entering reproductive diapause, females arrest reproduction coupled with changes in other traits such as cryptic colour pattern, large body size, increased fat deposits, increased longevity, and reduced behavioural activity for the entire dry season until the onset of the rains (Brakefield & Reitsma, 1991;Oostra et al, 2014;van Bergen et al, 2017). The induction of diapause and correlated expression of relevant traits is dependent on the availability of environmental cues, mainly temperature in the case of B. anynana, that reliably predict the future adult environment (Brakefield & Reitsma, 1991; for temperate insects, see Nylin, 2013).…”
Section: Species Of the African Mycalesina Genus Bicyclus Inhabit Bothmentioning
confidence: 99%
“…In contrast, the dry season form generally lack these eyespots, and they rely mainly on crypsis when at rest on dead leaf litter for survival against predators hunting by sight (Lyytinen et al, 2003(Lyytinen et al, , 2004Prudic et al, 2015). Along with the wing pattern changes, both forms differ in a suite of other morphological, behavioural, physiological and life-history traits, as an integrated response which is linked by a common hormonal switch as has been extensively explored in laboratory settings in a single species Bicyclus anynana (Oostra et al, 2010(Oostra et al, , 2014van Bergen & Beldade, 2019;van Bergen et al, 2017). Such an integrated system helps to maintain a season-specific adaptive phenotype by making use of environmental cues to predict approaching seasonal shifts (Brakefield & Reitsma, 1991;Kooi & Brakefield, 1999).…”
mentioning
confidence: 99%
“…Temperature experienced during the late larval stage is an important environmental inducer of the seasonal forms both in the field and in the laboratory; lower or higher temperatures act as a cue for forthcoming dry or wet seasons, respectively (Kooi andBrakefield 1999, Brakefield et al 2007). Moreover, developmental plasticity in mycalesine butterflies involves coordinated responses of morphological, physiological, behavioural and life history traits which together provide an adaptive response to climate instability (Oostra et al 2014, Mateus et al 2014, Nokelainen et al 2018, van Bergen and Beldade 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Both adult wing pattern and life history are determined by developmental temperature, although life-history traits retain the ability to acclimatize over the course of several weeks when environmental conditions change during adult life (e.g., Fischer et al 2003). Recently, we showed that Ecdysteroid hormones during the pupal stage play a functional role in regulating developmental plasticity of adult reproductive strategy, a role for this hormone that had already been established for wing pattern plasticity (Oostra et al 2014b). This indicates that, at least in B. anynana, developmental plasticity of wing pattern and of life history share developmental-physiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%